Urejanje prostora v malih mestih - institucija medobčinskega sodelovanja - Rus, Angelca (Urbani izziv, 1994)
The article deals with problems of intermunicipal cooperation, especially in the field of physical planning and land management, since the majority of urbanised areas and functional connections between new communes exceed the administrative boundaries of particular territorial units. Possibilities of cooperation are shown, aspects which should be respected when deciding upon cooperation, criteria for including peripheral communes into the municipal region and goals of improving intermunicipial cooperation. In the conclusion, the intermunicipial union is discussed, especially its tasks, criteria for shaping the union and the timing of accession.
Keywords: local government; lokalna samouprava; občine; povezovanje; prostorsko planiranje; prostorsko urejanje; spatial planning